Investigation of an outbreak of cutaneous anthrax in Banlu village, Lianyungang, China, 2012 - Qi Fang; Ying Liang; Bao Chang-jun; Zhang Ming-lei; Li Li; Cui Liang-liang; Zhang Ting-lu (Western Pacific Surveillance and Response, 2012)
Objective: After notification of a suspected case of anthrax following the slaughtering of a sick cow in Banlu village, an area that has not had any anthrax cases for decades, we aimed to confirm the outbreak, determine the transmission mechanism and implement control measures.Methods: The outbreak response team interviewed all people that had contact with the sick cow. Three types of cases’ specimens were collected and tested by blood smear, real-time polymerase chain reaction (PCR) and the gold colloid method. Traceback of potentially contaminated meat and cattle were conducted.Results: There were five confirmed and three probable cases verified among 17 people who had contact with the sick cow – an attack rate of 47%. The incubation period ranged from one to eight days with a median of two days. All eight cases had lesions. All were native residents of Banlu village aged between 21 and 48 years. Five male cases were professional butchers; two females and one male were temporary assistants. The sick cow’s meat and hide, as well as all cattle processed at the same time, were recalled. Hypochlorite was used to disinfect the contaminated environments, butchering facilities and the contacts’ personal effects.Conclusion: This outbreak was caused by anthrax bacillus transmitted to contacts from the tissues of the sick cow. Control of the outbreak was managed by recalling all potentially infected meat and disinfecting the slaughter house and the suspected cases’ personal effects and environment.